"Healing is a Done Deal": Temporality and Metabolic Healing Among Evangelical Christians in Samoa. Issue 2 (3rd March 2016) - Hardin, Jessica
ABSTRACT: Drawing on fieldwork in independent Samoa, in this article, I analyze the temporal dimensions of evangelical Christian healing of metabolic disorders. I explore how those suffering with metabolic disorders draw from multiple time-based notions of healing, drawing attention to the limits of biomedicine in contrast with the effectiveness of Divine healing. By simultaneously engaging evangelical and biomedical temporalities, I argue that evangelical Christians create wellness despite sickness and, in turn, re-signify chronic suffering as a long-term process of Christian healing. Positioning biomedical temporality and evangelical temporality as parallel yet distinctive ways of practicing healing, therefore, influences health care choices.